The Effect of Malathion on the Weight, Fecundity and Longevity of Ischiodon scutellaris Fabr. (Diptera: Syrphidae) - Hoe, Teh Kah; Ming, Eng Sook; Sudderuddin, Khwaja Ismail (1983)
The effects of sub-lethal doses of malathion on the weight, fecundity and longevity of Ischiodon scutellaris Fabr. were studied. The LDso values for malathion, applied topically to the third instar larvae, were 26.9 X 10-2 (24h) and 18.7 x 10-2 (48h) /lg/larva; the LD9S values were 146 X 10-2 (24h) and 127.6 X 10-2 (48h) /lg/larva. There was a significant difference (at 5% level) in the weight and longevity of female flies treated, at the third larval instar stage, with different doses of malathion. A similar weight difference (at 5% level) was noted between pupae treated at the larval stage. Measurable latent toxicity was evident for malathion. The LDso for direct toxicity was 41.7 X 10- 2 /lg/larva and for total toxicity it was 21.4 X 10-2 /lg/larva.